A multicenter randomized trial comparing the effectiveness and safety of a novel vascular closure device to manual compression in anticoagulated patients undergoing percutaneous transfemoral procedures: The CELT ACD trial. Issue 5 (15th March 2017) - Wong, Shing Chiu; Laule, Michael; Turi, Zoltan; Sanad, Wasiem; Crowley, James; Degen, Hubertus; Bennett, Kathleen; Coleman, Jim E.; Bergman, Geoffrey
Abstract : Objectives: This study compared the performance of Celt ACD ®, a novel stainless steel based vascular closure device versus manual compression (MC) for femoral arteriotomy site hemostasis in patients undergoing percutaneous coronary procedures. Background: Optimal access site management after percutaneous transfemoral procedures remains controversial. Methods: Patients enrolled in this multicenter, randomized open label trial underwent 6‐F diagnostic or interventional procedures and were assigned 2:1 to Celt ACD ® versus MC. All patients were on full anticoagulation. The primary efficacy end point was time to hemostasis (TTH) and the primary safety end points were 30‐day incidence of major procedural and access site related complications. Results: The trial allocated 207 patients to Celt ACD ® ( n  = 148) versus MC ( n  = 59) at 5 investigational sites. Baseline characteristics of the two groups were similar. Median TTH was 0 (Interquartile range (IQR): 0, 0.33) in the Celt ACD ® compared to 8 min (IQR: 0, 20; P  < 0.0001) in the MC group. Procedural success was 99.3% in the Celt ACD ® versus 98.1% in the MC group ( P  = NS). There was a single major adverse event due to device maldeployment and embolization with successful percutaneous retrieval. The 30‐day major complication rate was 0.7% in the Celt ACD ® and 0% in the MC group ( P  = NS). Conclusions: After 6‐F percutaneous invasive procedures in fully anticoagulated patients, TTH was significantly reduced in patients assigned to Celt ACD ® compared to patients managed with MC. The 30‐day rates of vascular complications were similarly low in both groups. (CELT ACD Trial; NCT01600482) © 2017 Wiley Periodicals, Inc.